The impact of the agricultural minimum wage and the role of enforcement in South Africa - Stanwix, Benjamin (School of Economics, 2015)
Since 1999 South Africa gradually developed a detailed minimum wage schedule covering eleven sectors of the economy. Labour market institutions were also created to enforce the new laws; the efficacy of which has hitherto remained unexamined. The legislated minimum wage in South Africa varies across, and within sectors. Mandated wages within a sector can differ depending upon occupation type, the number of hours worked, as well as geographic location. There is thus no single national minimum wage. Internationally, minimum wages are widely used as a policy tool to protect vulnerable workers from exploitation and help alleviate poverty. In South Africa the socioeconomic arguments supporting minimum wages are well established, that is, minimum wages aim to redistribute earnings to low paid workers, assist workers with weak bargaining power, and lift the working poor out of poverty. The economic effect that minimum wages have, on employment in particular, is a classic labour economics question which has attracted considerable attention in the international literature. However, as the two introductory quotes illustrate, there is some disagreement among economists as to the precise impact of minimum wages. More broadly there are those who question whether minimum wages are a welfare enhancing intervention at all. The recent introduction of minimum wage laws in South Africa makes comprehensive enquiry into such issues particularly pertinent for economists and policymakers. It is therefore surprising that few empirical studies have investigated the impact of these policies on the local labour market. In an effort to begin filling the gap this paper focuses on the agricultural sector in South Africa. The first component of this paper investigates and measures the aggregate impact of the Agricultural Sectoral Determination. Observing changes in farmworker earnings, contract coverage, employment, and the number hours worked per week, provides insight into the impact of the law. These changes are examined using data from the South African Labour Force Surveys (LFS) 2000-2007 which includes three years before the law was introduced and four years afterwards. Descriptive statistics and difference-in-differences regressions are used to analyse the impact of the law. A control group, made up of similar workers not subject to the law, is used for comparison. Results show that the Sectoral Determination caused significant growth in average farmworker earnings and an increase in the number of workers holding written employment contracts. However, the probability of agricultural employment for a typical worker appears to have fallen, while hours worked were unaffected. After analysing these changes, the second component of the paper examines the associated and underexplored issue of enforcement and compliance. The number of farmworkers receiving sub-minimum wages (i.e. noncompliance) in South Africa is high and thus the observed impact of the law can be seen as a lower bound. I test to see whether the increase in wages which occurs over the period can be linked to formal enforcement of the Sectoral Determination.